Asian tigers' choices: An overview - Hwee Kwan Chow (Asian Development Bank Institute (ADBI), 2010)
This paper considers the choices facing the Asian tiger economies regarding growth strategies that foster trans-Pacific rebalancing. A review of historical data spanning 2000 to 2008 reveals only a slight widening of the overall current account surplus but that there is considerable variation across the countries, with Hong Kong, China exhibiting the biggest increase in the saving and investment (S-I) balance. Meanwhile, cross-correlation coefficient estimates tentatively suggest that changes in the real effective exchange rate do not seem to exhibit a consistent negative lead over changes in the S-I gap in the short run over the past decade. High import leakage, particularly for the ultra small, open economies of Hong Kong and Singapore, calls into question the scope for recalibrating growth drivers towards domestic demand. Nonetheless, the implementation of structural policies such as those aimed at raising the productivity and wages of workers in the services industry as well as the introduction of financial products that alleviates the need for precautionary saving can induce domestic consumer demand, especially for the larger economies of Korea and Taipei,China. Moreover, the rising affluence and living standards in fast growing regional economies such as the People's Republic of China (PRC) offers the Asian tigers the potential of gearing their trade structure in final goods towards markets in the region, thereby aiding the reduction in trans-Pacific imbalances.
Keywords: F32; F41; F43; 330; Wirtschaftswachstum; Wachstumspolitik; Wirtschaftspolitisches Ziel; Hongkong; Singapur; Südkorea; Taiwan